Development of an LC-MS/MS method for amantadine detection in human plasma using ZIF-8 as adsorbent and pharmacokinetic investigation - Wang, Zhengang; Han, Huanmei; Li, Hongxia; Xu, Wenjuan; Ding, Kuiying (Frontiers in Pharmacology, 2026)
In this study, a liquid chromatography-tandem mass spectrometry (LC-MS/MS) method was developed and validated for the quantitative determination of amantadine in human plasma, with the incorporation of an internal standard to improve analytical accuracy. Plasma samples collected from volunteers were processed using acetonitrile-methanol (3:1, v/v) as the extraction solvent, followed by protein precipitation and purification via the QuEChERS (Quick, Easy, Cheap, Efficacious, Rugged, and Safe) method. Analysis was performed using LC-MS/MS under multiple reaction monitoring mode, with a total run time of 8 min. Quantification was carried out using the internal standard method. After a single oral administration of 200 mg amantadine hydrochloride, plasma concentrations were measured at various time points. Pharmacokinetic parameters were derived by fitting the data to a pharmacokinetic model using specialized software. The results demonstrated good linearity over the range of 0.5–20 ng/mL, with a correlation coefficient (R2) of 0.9978. The extraction recovery ranged from 94.5% to 110.1%, and both intra-day and inter-day relative standard deviations (RSD) were below 10%. The limit of detection (LOD) and limit of quantification (LOQ) were 0.15 ng/mL and 0.5 ng/mL, respectively. The absorption and elimination processes of amantadine in plasma followed first-order kinetics, with R2 > 0.9. Notably, gender-specific differences were observed in the time to maximum concentration (Tmax) and maximum concentration (Cmax): females achieved a Cmax of 670.23 ng/mL at 4 h, whereas males reached a Cmax of 650.87 ng/mL at 8 h. This LC-MS/MS method is simple, rapid, and accurate, rendering it suitable for pharmacokinetic studies of amantadine in humans. Additionally, the established kinetic model provides valuable references for clinical medication guidance.